Handheld pH‐Meter‐based Electrochemical Aptasensing of Carcinoembryonic Antigen on Multifuctional Magnetic Beads. Issue 10 (12th May 2022) - Chen, Shaobo; Lin, Shujin; Han, Xiao; Han, Xianlin
Abstract: Methods derived from immunoassays and aptasensors have been established for monitoring of carcinoembryonic antigen (CEA) in biological fluids, but most involved complex procedure and various reactions. We designed an uncomplicated and convenient electrochemical aptasensing platform for the quantitative monitoring of CEA on multifunctionalized magnetic beads with a handheld pH meter as the read‐out. Initially, CEA‐specific aptamers were covalently conjugated to magnetic beads, and then hybridized with glucose oxidase‐labeled complementary strands to construct multifunctional nanoprobes. After addition of target CEA, the analyte interacts with the corresponding aptamer and then release the complementary strand. After magnetic separation, the released glucose oxidase‐labeled complementary strands hydrolysed glucose, thereby leading to a change in pH of the detection solution, which was quantitatively monitored on a hand‐held pH meter. Under the optimum conditions, the aptasensor based on pH meter exhibited well responses relative to CEA concentrations inside the dynamic range between 0.01 and 100 ng mL −1 and detection limit at least 9.3 pg mL −1 . Good duplicability, high specificity and ability for long‐term stable storage are obtained for the as‐prepared aptasensors. Additionally, human serum specimens were determined through pH‐meter‐based aptasensors, and the results closely matched the commercial enzyme‐linked immunosorbent assay (ELISA) of human CEA. Abstract :